PM3 and DFT Computational Studies of the Reaction Mechanism of Formaldehyde and Isoleucine - Umar Hamza; Adamu Uzairu; Muhammad S. Sallau; Stephen E. Abechi; Gideon A. Shallangwa (Aceh International Journal of Science and Technology, 2016)
The reaction of formaldehyde and Isoleucine was studied using semi-empirical and density functional theory methods. Possible reactive sites are proposed and reaction mechanism postulated. It was found that the Isoleucine nitrogen attacks the carbonyl carbon of formaldehyde and forms a methylol intermediate that undergoes a condensation with another Isoleucine to produce a Methylenediisoleucine through a methylene bridge (cross-linking). The enthalpies of the reaction are -78.79 kJ/mol and -39.14kJ/mol for PM3 and DFT respectively also ΔSo and ΔGo, for the PM3 and DFT studies predicted. The reaction was found to be exothermic and second order.